The development of African private enterprise - Geiger, Theodore; Armstrong, Winifred (Washington : National Planning Association, 1964)
This study, covering 37 tropical African countries, surveys the development of indigenous private enterprise in industry, distribution and the service trades. Agriculture - by far the largest private sector in these countries - is excluded on the grounds that it "can more effectively be dealt with in the context of rural development as a whole". The first portion of the study elaborates an unblushing classic case for private enterprise: "basically, the benefits of private enterprise . . . arise from the nature of human motivations". A review of the characteristics and problems of African enterprise (with special attention to Ghana, the Ivory Coast, Kenya, Liberia, Nigeria, Senegal, Tanganyika and Uganda) is followed by a series of enterprise-encouraging recommendations to African entrepreneurs, African governments, foreign investors, foreign governments and international agencies.
Includes bibliographical references: 154-156.
lje 16/01/2018
Loans
Keywords: Industrial policy; Industries